Therapeutic Approaches Through the Use of Horses in the Recovery of Children with ASD - (Moses) Munteanu, Valentina-Beatrice (New Trends in Psychology, 2022)
Hippotherapy is one of the modern techniques of therapy and is used to relieve and treat the symptoms of people with motor and neuro-motor deficiencies. As a result of using hippotherapy, the effects can sometimes be observed, marking in the case of people with disabilities, both physical and mental benefits. People can socialize much more easily, become aware of their body due to the interaction with the horse and also gain more control over their own body, they communicate more easily.